The Determinants of Mobile E-Wallet Adoption Across Generation, A Lesson Learned From Indonesia - Arini, Nur; Hilendri Lestari, Baiq Anggun; Hanani, Tri (Ilomata International Journal of Tax and Accounting, 2024)
The use of e-wallets has an impact on the ease of transactions. Various kinds of transactions can be done through this application. However, despite the convenience offered, e-wallet adoption remains low. This study aims to determine what factors influence the determinants of mobile e-wallet adoption across generations in Indonesia. The study was investigated using a composite model based on the diffusion of innovation theory (DIT), technology acceptance model (TAM) and information system success model (ISSM). Data was collected from 200 e-wallet users in West Nusa Tenggara province and analyzed using multiple linear regression (PLS-SEM). The results showed that the use of e-wallets was not affected by observability, relative advantage, information quality and system quality. Ease of use and perceived usefulness have a positive impact on the decision to use e-wallets in Indonesia. The results of this study are very important to assess the situation and prospects of e-wallets in Indonesia. The results of this study offer significant insights for policy makers and e-wallet service providers to develop appropriate strategies to increase e-wallet users in Indonesia.